Satisfaction on Clinical Learning Environment among Students in Selected Nursing Colleges, Kathmandu - Neupane, Kalpana; Onta, Mandira; Darshandhari, Gayetri (Journal of Nursing Education of Nepal, 2023)
Introduction: Clinical learning is an essential component of nursing studies. Satisfaction with clinical placements may improve students’ learning outcomes as well as their retention in nursing studies. The objective of this study was to find out the satisfaction regarding the clinical learning environment among students in selected nursing colleges, in Kathmandu. Methods: Descriptive cross-sectional study was conducted among 92 nursing students studying in three Tribhuvan University Affiliated nursing colleges in Kathmandu. Respondents were selected by using the total enumeration method. Data were collected using a structured self-administered questionnaire and analyzed using SPSS version 16 and analysis was done by using descriptive and inferential statistics. Results: The findings of the study showed that only 30.4% of respondents had a high level of satisfaction on clinical learning environment. There was a significant difference between students’ satisfaction with age (p= 0.030) and areas of clinical practicum (p=0.0001). According to domain highest satisfaction was obtained in nursing care on the ward (3.89±0.51) and the lowest satisfaction was obtained in supervisory relationships with students (3.46±0.59). Conclusion: Satisfaction level of students needs to be increased because this study reveals that only one third of the nursing students have a high level of satisfaction with their clinical placement. A significant difference was found between age and areas of clinical practicum. DOI: https://doi.org/10.62143/2jk2n606